Pengaruh Penerapan Model Kolaboratif MURDER terhadap Hasil Belajar, Aktivitas dan Respons Siswa dalam Pembelajaran Matematika Kelas X - Muawiah Inda Magfirah; Muhammad Darwis M; Rusli (Issues in Mathematics Education (IMED), 2020)
This study aims to determine the effect of the application of MURDER collaborative model (Mood, Understand, Recall, Detect, Expand, and Review) on student learning outcomes, activities, and responses in learning mathematics in class X. This research is pre-experiment with quantitative approach with techniques sampling is cluster random sampling. Data collection was carried out using observation sheets of implementation of learning, test results of learning (pretest and posttest), observation sheets of student activities, and student questionnaire responses. The data analysis technique used is descriptive and inferential statistical analysis. The results of descriptive statistical analysis showed: (1) the average of learning achievement was 3,73 (well implemented), (2) the average pretest results were 35 (very low category). The average posttest results was 85 (high category), (3) the posttest results show that classical completeness is achieved 94% (4) the average normalized gain is 0,77 (high category), (5) the average percentage of activity students by 90% (very active) (6) the average percentage of students who gave positive response 89%. The results of inferential statistics analysis show: (1) the average value of students taught using collaborative MURDER model was greater than 70, (2) the normalized gain average value was greater than 0,3 (medium category), (3) the average classical completeness greater than 80%. In general it can be concluded that implementation MURDER collaborative model has an effect on students mathematics learning outcomes, activities, and responses.